Microfracture of Articular Cartilage. Issue 6 (28th June 2016) - Sommerfeldt, Mark F.; Magnussen, Robert A.; Hewett, Timothy E.; Kaeding, Christopher C.; Flanigan, David C.
Abstract : Microfracture is a treatment option for symptomatic, full-thickness cartilage defects. Microfracture is most likely to be successful when performed in nonobese patients under the age of thirty years for small (<2 to 4-cm2) femoral condylar defects that have been symptomatic for a short time (less than twelve to twenty-four months). Microfracture has acceptable short-term clinical results, but results can be expected to decline over time. Long-term studies that compare microfracture with advanced cartilage restoration techniques are required to ascertain whether these newer techniques provide longer-lasting results.